EFFECTIVENESS OF USING YOUNG COCONUT WATER AS A NATURAL STIMULANT ON THE FECUNDITY AND HATCHING RATE OF MANDALIKA CATFISH EGGS - Ni Kadek Puji Astuti; Aminullah Aminullah; Ramadhan Ramadhan (Universitas Mataram, 2026)
The high cost of synthetic hormones and the difficulty of standardizing pituitary methods are obstacles in the cultivation of Mandalika catfish. Young coconut water (Cocos nucifera) contains phytohormones, amino acids, and minerals that have the potential to act as natural stimulants to stimulate the endocrine system and improve fish reproductive performance. This study aims to evaluate the effectiveness of using various stimulants on fecundity, hatching rate, and hatching time of catfish eggs, as well as to monitor the stability of water quality during the incubation process. This experimental study used a Completely Randomized Design (CRD) with three treatments: commercial hormones (P1), young coconut water (P2), and pituitary gland (P3). The doses used were 0.5 ml/kg for female broodstock and 0.3 ml/kg for male broodstock intramuscularly. The results showed that young coconut water (P2) gave the best results with an average fecundity of 20,125 eggs, significantly higher than P3 (10,250 eggs) and P1 (10,000 eggs). The highest hatching rate was also achieved by treatment P2 at 83.00%, followed by P3 (71.75%) and P1 (71.00%). Egg hatching time ranged from 31 to 34.25 hours, with P1 recording the fastest time but the lowest hatching rate. Water quality parameters were optimally maintained throughout the study at a temperature of 26–27°C, pH 6.5, and DO 3 mg/L. Young coconut water has proven to be the most effective natural stimulant in increasing the quantity and quality of Mandalika catfish reproduction, while also offering a cost-effective and environmentally friendly solution for farmers.